From Little Things Big Things Grow: Creating Lifelong Responsive Musical Experiences. Issue 1 (March 2014) - Klopper, Christopher
The Australian story of the Gurindji strike pertains to a seven-year protest by the Gurindji people, led by elder Vincent Lingaiari, demanding a return of Indigenous land that had been placed under the control of pastoralists from the late 1800s. The story of their struggle was captured by the composers Kev Carmody and Paul Kelly in 1993 in a song titled From Little Things Big Things Grow – which relates the story in terms of Australian popular ideals of mateship, courage, the battler, a fair go, the underdog getting one over on the powerful and a happy ending where the hero wins. This article uses the song by Carmody and Kelly as a metaphor for considering recent international research in musical education, music teaching and learning processes. Specifically, the author is interested in how current research captures the musical experiences of children, teachers and parents in a multiplicity of educational settings to create lifelong responsive musical experiences. Drawing on themes from the Carmody and Kelly song, in dialogue with recent international research in the field of music education, he illuminates how the master-apprenticeship relationship of interdependence, courage, commitment and access offers the potential for a happy ending where music education is the hero.